2009
DOI: 10.3758/mc.37.6.715
|View full text |Cite
|
Sign up to set email alerts
|

Classification as diagnostic reasoning

Abstract: An ongoing goal in the field of categorization has been to determine how objects' features provide evidence of membership in one category versus another. Well-known findings include that feature diagnosticity is a function of how often the feature appears in category members versus nonmembers, their perceptual salience, how features are used in support of inferences, and how observable features are related to other observable features. We tested how diagnosticity is affected by causal relations between observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…Consistent with this interpretation, Heit and Bott found that learners classified a feature as "Doe" even if it was never observed during training so long as their prior knowledge indicated that it was typical of churches. Other studies provide evidence of the inferences in service of classification that knowledge supports (Rehder & Kim, 2009;Rehder & Ross, 2001). Indeed, recall Murphy and Medin's (1985) example of classifying a partygoer who jumps into a pool as drunk-one reasons from aberrant behavior to its underlying cause even if one has never before observed drunken swimming.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this interpretation, Heit and Bott found that learners classified a feature as "Doe" even if it was never observed during training so long as their prior knowledge indicated that it was typical of churches. Other studies provide evidence of the inferences in service of classification that knowledge supports (Rehder & Kim, 2009;Rehder & Ross, 2001). Indeed, recall Murphy and Medin's (1985) example of classifying a partygoer who jumps into a pool as drunk-one reasons from aberrant behavior to its underlying cause even if one has never before observed drunken swimming.…”
Section: Discussionmentioning
confidence: 99%
“…A second basis for predicting a larger causal status effect in the Essentialized-Chain-80 condition stems from the fact that we expected that participants might construe the classification test as a causal reasoning task. For example, Rehder and Kim (2009a) found that a feature was more diagnostic of category membership when it was caused by an underlying essential feature because participants reasoned backwards from the observed to the essential feature and decided category membership on that basis. This implies a stronger causal status effect in the present EssentializedChain-80 condition because only feature X provides direct inferential support for E, contributing further to X's greater classification weight relative to Y and Z.…”
Section: Methodsmentioning
confidence: 99%
“…Objects that are likely to have been generated by a category's causal model are considered to be good category members, and those unlikely to be generated are poor category members. Quantitative predictions for the generative model can be derived assuming a particular representation of causal relations first introduced by Cheng (1997) and later applied to a variety of categorybased tasks (Rehder, 2003a(Rehder, , 2003bRehder, 2009;Rehder & Burnett, 2005;Rehder & Hastie, 2001;Rehder & Kim, 2006, 2009a. For example, for the causal model in Figure 1, assume that the causal mechanism relating feature j and its parent i operates (i.e., produces j) with probability m ij when i is present and that any other potential background causes of j collectively operate with probability b j .…”
mentioning
confidence: 99%
“…Their conclusion that complexity facilitates learning when the dimensions are organized in a coherent manner may arise because the intercorrelated complex generates a prototype-like representation or integrated unit that better maintains memory for later judgments that tap these relations. The introduction of shaping variables (Homa, 1984), such as category size, pattern variance, and so forth, and the manipulation of the types of associated features, such as causal links (Rehder & Kim, 2009), when combined with categorical structure variables as in the present study, might further elucidate conditions that foster the category label as a special feature. A theoretically productive line of research might be to build in feature correlations, as in the present study, modified (perhaps by instructions) such that some, but not all, features were causal.…”
Section: Test Label Test Featurementioning
confidence: 95%